Merry Christmas, Splat - Scotton, Rob. (New York, N.Y. : HarperCollins, 2009)
Splat the cat is worried that he has not been good enough to deserve a visit and a present from Santa Claus.
Keywords: Cats -- Fiction; Christmas -- Fiction; Behavior -- Fiction